Research methods a practical guide for students and researchers - Tan, Willie (World Scientific, 2022)
Research Methods: A Practical Guide for Students and Researchers is a practical guide on how to conduct research systematically and professionally. The book begins by distinguishing between causal and interpretive sciences. It then guides the reader on how to formulate the research question, review the literature, develop the hypothesis or framework, select a suitable research methodology, and analyze both quantitative and qualitative data. The book uses classic examples as exemplars. It also uses many examples from different disciplines and sectors to demonstrate and showcase the inter-connections and wider applications of research tools. The book emphasizes integration. It does not merely provide a smorgasbord of research designs, data collection methods, and ways to analyze data. Instead, it shows how one could formulate research strategies given the outcomes the researchers are required or tasked to deliver. The revised edition includes three new chapters on time series (including spatial models), machine learning, and meta-analysis. In addition, existing chapters have been expanded to include more examples, digital research, and new material